2012
DOI: 10.1155/2012/758349
|View full text |Cite
|
Sign up to set email alerts
|

Study of Heavy Metal Levels among Farmers of Muda Agricultural Development Authority, Malaysia

Abstract: Heavy metals, particularly cadmium, lead, and arsenic, constitute a significant potential threat to human health. This study was conducted to determine the levels of cadmium, lead, and arsenic in nail samples from farmers at Muda Agricultural Development Authority (MADA), Kedah, Malaysia, and evaluate factors that can contribute to their accumulations. A total of 116 farmers participated in this study. Inductively coupled plasma mass spectrometry (ICP-MS) was used to analyze concentration of heavy metals in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 17 publications
5
9
2
Order By: Relevance
“…This can be seen through the concentrations of Pb among adult females in Kuching and Kota Samarahan which were still within the acceptable range. The concentrations showed that they were in good agreements to literature values of healthy and non-smoking participants (Afridi et al, 2008;Goulle et al, 2009), besides having the results in this study not as high as Pb concentrations found in occupationally-exposed individuals (Abdulrahman et al, 2012;Ghazali et al, 2012;Skalny et al, 2015).…”
Section: Elemental Concentrations In Fingernailssupporting
confidence: 88%
See 1 more Smart Citation
“…This can be seen through the concentrations of Pb among adult females in Kuching and Kota Samarahan which were still within the acceptable range. The concentrations showed that they were in good agreements to literature values of healthy and non-smoking participants (Afridi et al, 2008;Goulle et al, 2009), besides having the results in this study not as high as Pb concentrations found in occupationally-exposed individuals (Abdulrahman et al, 2012;Ghazali et al, 2012;Skalny et al, 2015).…”
Section: Elemental Concentrations In Fingernailssupporting
confidence: 88%
“…However, when the results of Pb in adult females in this study were compared to that of another Malaysian study, the results in the latter research was reported to be higher, which was 6.2 ± 5.2 µg/g (Ghazali et al, 2012). This may be due to the occupational exposure of research participants involved in their study.…”
Section: Elemental Concentrations In Fingernailscontrasting
confidence: 61%
“…However, previous study has reported that in occupational exposure to cadmium or lead, antioxidant potential of the body is disturbed, which is manifested by changes in both the concentration of trace elements and the activity of some enzymes (Wąsowicz, Gromadzińska, & Rydzyński, 2001). However, study among farmers from MADA Kedah showed heavy metals (cadmium, lead and arsenic) were within normal range (Ghazali et al, 2012). In a study on the levels of selenium in toenails, it was also said that the tobaccos in cigarettes could disrupt the absorption of selenium (Ghandirian et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…A 1000 mg/l stock solution was prepared for each heavy metal (MERCK Titrisol). Samples were stored in metal-free plastic tubes at room temperature until the determination of heavy metals [4].…”
Section: Determination Of Heavy Metalsmentioning
confidence: 99%